About intellectuals and politics in Peru - Gonzales Alvarado, Osmar (1997)
Reflecting on the relationship alluded to in the title of this article is risky and difficult. Risky because it is possible not to achieve the necessary prudential distance for the analysis and because, in part, it is talking about a matter that concerns experientially; difficult because generalizing can lead us to ignore important circumstances and nuances that have to do with the different times, with the different types of intellectuals and with the variety of ways they have of relating to politics. In this way, the links of intellectuals with politics must be studied in a long historical line that must be delimited by the type of intellectual that emerges at each moment. In other words, the problem (intellectual-political relationship) must be provided with historical density. And this is a whole research program.